3 - L’approche par les besoins essentiels, une théorie nouvelle de développement pour la décennie 1980 ? - FOUNOU-TCHUIGOUA, Bernard (Africa Development, 1980)
The author wants to show the contradictions of basic needs approach in various aspects. Firstly, on a purely theoretical basis, it supposes a transfer of values from a high labour productivity sector (formal sector) to a low labour productivity sector (informal sector) which is not demonstrated. It also supposes an auto nomous concentration of the informal sector, which is erroneous. Secondly, countries with no large financial resources and/or cheap labour and/or high potential extension of the interior market (which is the case the majority of African countries) cannot benefit from programmes built on the theory of basic needs and even less on this strategy for development. On this point, a few examples on the problem of technology and food self sufficiency are given. Thirdly, a few prerequisites of the theory (democracy, equality, etc...) are inconsistent with maintaining the relationships of exploitation (not ques tioned by the theory) which govern the links between the Centre and the Periphery. On the contrary, they are consistent with the conditions for the recovery of economic growth in the Centres with the dismantling of the eco nomic front which the Periphery has been trying to set up since 1973. The author concludes that the means for salvation lie in a self-centered development which Africa can achieve only if it builds, at least on a regional basis, large political units but not the so-called common markets.